Life zone and habitat disturbance do not explain the coexistence in Sturnira bat species - Mosquera Izquierdo, Esteban (2022)
One of the key questions in ecology is to understand the mechanisms that modulate the coexistence between syntopic species. Climate and habitat perturbation gradients have been proposed as moderators of species coexistence. The first is related to time availability and the diversity of food resources. The second is related to change in habitat structure that promotes changes in plant structure and diversity that impacts the diversity of other organisms. Although there is empirical evidence that supports these mechanisms to explain coexistence, they have not been evaluated quantitatively and on a wide geographic scale. Using phytophagous bat species of the genus Sturnira we evaluated both mechanisms. These bats are morphologically similar and are key organisms for the seed dispersal of Neotropical Forest plants. Using systematic review protocols, we obtained data of the occurrence and relative abundance of syntopic Sturnira species of different Neotropical forests. We used generalized linear models to evaluate the predictor power of Holdridge's life zones and habitat disturbance type to explain the evenness of syntopic Sturnira species. We found a highly Sturnira species evenness across life zones, going from 0.68–0.92, and found life zones with a maximum of eight Sturnira species coexisting in the same type of forest. The life zones and the type of disturbance do not explain the variation of evenness in Sturnira species. These results suggest that there is not a competitive exclusion among Sturnira species in tropical forests, and despite their ecological niche similarity, the environment allows the coexistence among these highly related species.